Application international conventions against own rules of international e-commerce portal Corporate - Bolaños Arturo, Giovanni Hernán (2023)
This paper seeks to make a briefly reflection on the impact that is generating the international business, the use of electronic trading platforms. At the same time, the impact it can generate the application of international instruments as the “United Nations Convention on the use of Electronic Communications at International Contracts of 2005” against the scope of applicability of United Nations Convention on Contracts for the international sales of goods (Cisg) known as the Vienna Convention of 1980 like the own electronic Regulations, uses and ecommerce international practices to these case as it is www.Alibaba.com.